Delineating the Association Between Soluble CD26 and Autoantibodies Against G-Protein Coupled Receptors, Immunological and Cardiovascular Parameters Identifies Distinct Patterns in Post-Infectious vs. Non-Infection-Triggered Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Szklarski, Marvin; Freitag, Helma; Lorenz, Sebastian; Becker, Sonya C.; Sotzny, Franziska; Bauer, Sandra; Hartwig, Jelka; Heidecke, Harald; Wittke, Kirsten; Kedor, Claudia; Hanitsch, Leif G.; Grabowski, Patricia; et al. (Frontiers in Immunology, 2021)
Soluble cluster of differentiation 26 (sCD26) has a wide range of enzymatic functions affecting immunological, metabolic and vascular regulation. Diminished sCD26 concentrations have been reported in various autoimmune diseases and also in Myalgic Encephalomyelitis/Chronic fatigue syndrome (ME/CFS). Here we re-evaluate sCD26 as a diagnostic marker and perform a comprehensive correlation analysis of sCD26 concentrations with clinical and paraclinical parameters in ME/CFS patients. Though this study did find significantly lower concentrations of sCD26 only in the female cohort and could not confirm diagnostic suitability, results from correlation analyses provide striking pathomechanistic insights. In patients with infection-triggered onset, the associations of low sCD26 with elevated autoantibodies (AAB) against alpha1 adrenergic (AR) and M3 muscarinic acetylcholine receptors (mAChR) point to a pathomechanism of infection-triggered autoimmune-mediated vascular and immunological dysregulation. sCD26 concentrations in infection-triggered ME/CFS were found to be associated with activated T cells, liver enzymes, creatin kinase (CK) and lactate dehydrogenase (LDH) and inversely with Interleukin-1 beta (IL-1b). Most associations are in line with the known effects of sCD26/DPP-4 inhibition. Remarkably, in non-infection-triggered ME/CFS lower sCD26 in patients with higher heart rate after orthostatic challenge and postural orthostatic tachycardia syndrome (POTS) suggest an association with orthostatic regulation. These findings provide evidence that the key enzyme sCD26 is linked to immunological alterations in infection-triggered ME/CFS and delineate a different pathomechanism in the non-infectious ME/CFS subset.